Augmented Reality as a Learning Media to Improve Vocabulary Learning Among Preschoolers - Abdulrazak Yahya, Saleh; Elaveni, Kasirajan (Springer, Cham, 2023)
Technology is crucial to education since it has spurred numerous innovations and advancements in the educational system. At the moment, augmented reality (AR) is thought to be one of the technologies that could have a significant impact on the field of education. The visual and interactive aspects of augmented reality, which enable the projection of digital content into the user's field of view, have enormous promise as educational tools. For students, especially young ones, it might be helpful to design simulations that keep them attentive and interested in what they are studying. Therefore, the goal of this study is to enhance pre-schoolers' vocabulary learning through the use of augmented reality. To accomplish the goal of this study, an AR application called the Home AR is created. The application's focus is on teaching the children between the ages of 4 and 6; the names of everyday objects are in four distinct languages: English, Malay, Tamil, and Chinese. The furniture and appliances that are found in the living room, bathroom, bedroom, and kitchen are chosen to be displayed in this application. To display the images of home goods that can be scanned from the AR application, flashcards are created as markers. The performance of the students utilising the developed application and the conventional learning approach is compared in an experimental study. Additionally, a variety of evaluation techniques are used to examine how parents, teachers, and pre-schoolers feel about adopting augmented reality (AR) as a learning tool for vocabulary development. The findings gathered for this study demonstrated that pre-schoolers can efficiently acquire languages through AR. The results show that AR has a high potential for use as a revenuegenerating medium in the future and can be used for learning.